The impact of modern agricultural technology promotion and adoption on agri-food system resilience - Zhang, Yuting; Shang, Juan; Yu, Ziling (Frontiers in Nutrition, 2025)
Enhancing agri-food system resilience holds profound strategic significance for ensuring food security in developing countries. This study constructs an evolutionary game model at the county level to theoretically explore the positive effects of modern agricultural technology promotion and adoption on agri-food system resilience. Based on panel data from 2,312 counties in China during the period 2006–2023, and using the National Modern Agricultural Demonstration Zone policy as a quasi-natural experiment, the study employs a multi-period difference-in-differences approach to rigorously investigate the effects and underlying mechanisms of modern agricultural technology promotion and adoption on agri-food system resilience. The empirical findings indicate that: (1) The diffusion of modern agricultural technologies significantly enhances agri-food system resilience, and this conclusion remains robust after a series of consistency checks. (2) Mechanism analysis shows that modern agricultural technology diffusion improves resilience by enhancing agricultural technological innovation capacity, increasing local government attention to agriculture, promoting agricultural financial development, and improving urban–rural coordination. (3) Heterogeneity analysis reveals that the positive impact of modern agricultural technology diffusion is more pronounced in counties with labor outflow, in non-major grain-producing regions, in the second and third batches of National Modern Agricultural Demonstration Zone, in Han Chinese districts, and in counties with higher levels of education. (4) Kernel density analysis demonstrates that modern agricultural technology diffusion has contributed to narrowing the disparities in agri-food system resilience across counties. These findings provide valuable empirical evidence and policy insights for developing countries seeking to bolster agri-food system resilience and safeguard food security.